Improving Well-Being in the United States - Caldera Sánchez, Aida (OECD Economics Department Working Papers, 2014)
Life is quite good in the United States compared to other OECD countries, thanks to strong economic growth and technological progress having lifted average income to high levels. Nonetheless, there is evidence that the benefits from growth have not been sufficiently broad based. Self-reported happiness increases with income, an issue particularly resonant in a country with among the highest levels of income inequality in the OECD and a pattern of inequality that appears to be moving toward even more concentration at the very top at the expense of the middle class and the poor. Working hours that remain among the longest in the OECD are also creating challenges for work-life balances, child education, personal care and leisure. These pressures are contributing to higher job strain and work-related stress with unhealthy consequences, including for mental health, and a detrimental impact on employability and medical costs. While these trends cannot be easily reversed, a number of policy options are being usefully rolled out and other initiatives are being considered: federal-level policies improving access to health care and early-childhood education, state-level initiatives favouring workplace flexibility, firm-level investments in job quality and greater attention to the health consequences of job-stress. If successfully adopted, they would go a long way toward improving the well-being of American working families. This Working Paper relates to the 2014 OECD Economic Survey of United States (www.oecd.org/eco/surveys/United States)